Arterial hypertension pregnancy induced at the Conjunto Hospitalar de Sorocaba. Maternal and perinatal aspects - Novo, Joe Luiz Vieira Garcia; Patrício, Bianca Totta; Vanin, Natália Sartori (Revista da Faculdade de Ciências Médicas de Sorocaba, 2010)
ABSTRACT Objectives: to contribute with the description and analysis of the risk factors associated with preeclampsia in the CHS. Methods: retrospective observational study of medical handbooks on the deliveries of pregnant women hospitalized in the CHS from January - February 2007 to August 2008. The variables being studied were: social demographic mother-to-be behavioral characteristics; family history, personal gestational obstetrics overview; deliveries, puerperal data; patient assistance conductibility, clinical development and mother/baby hospital discharge. The statistical analysis which made use of Statistical Package for Social Sciences came to these results: out of the 2122 performed deliveries, 246 patients presented preeclampsia. Hospital admittance being due to: hypertension crisis (31.30%), abdominal pain (26.02%) and eclampsia (2.04%). Hydralazine (15.85%) and magnesium sulfate (14.23%) were used to control hypertensive and convulsion crisis. Furthermore, gestational age (p = 0.037) and fifth minute Apgar index of newborns (p = 0.020) came out significantly higher in patients with no family history of hypertension. In the chi-square test (PAD >110 mmHg), there was significant difference in severe preeclampsia and eclampsia patients (p < 0.001), late maternal complications (p = 0.009) and newborn Apgar index in the first (p < 0.001) and fifth minutes (p < 0.007). Conclusion: in spite of the severe preeclampsia conditions some admitted patients presented, the CHS dealt with a small percentage of complications and mortality rate due to the use of magnesium sulfate and the successful handling of deliveries.